PILIHAN KODE BAGI SISWA DI PESANTREN ULIL ALBAB (KAJIAN SOSIOLINGUISTIK) - Baiq Yulia Kurnia Wahidah; D. Djatmika; Sri Marmanto (Prasasti: Journal of Linguistics)
This research aims to find and describe the selection of code in to three domains as well as the types of code choice in accordance with the context in the environment of Ulil Albab boarding schools. The data provision in this study is linguistic data from visual or audio visual recording by using taping and gathering method. The data is primary and secondary. Primary data is the result of visual or audio visual recording of the communicating interaction event and the secondary data is the result of previous research review.